Seroprevalence of antibodies IgG/IgM anti-T. gondii in women of Coro, Venezuela - Yotsabeth Saúl-Garcia; Coromoto Martínez-Leal; Neomar Semprún-Hernández; Dilia Martínez-Mendez (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2019)
Studies show a high frequency of IgG against T. gondii. The aim was to evaluate the seroprevalence of IgG and IgM anti-T. gondii in 522 women. 13% of seropositivity IgG+/IgM- and 0.7% IgG+/IgM+ was found. This could be due to the climate characteristics who